Cladocera Chydoridae of high altitude water bodies (Serra da Mantiqueira), in Brazil - SANTOS-WISNIEWSKI,M. J. (2002)
The diversity of species of Cladocera, Chydoridae in the water bodies belonging to the water management unity of Serra da Mantiqueira, was studied inside the BIOTA/FAPESP Program. A total of 21 water bodies were analyzed and the sampling was carried out between 9th and 11th September, 1999. Horizontal and vertical net hauls were taken at littoral and limnetic region in each lake. Most water bodies in Serra da Mantiqueira unity are small, shallow, and densely colonized by macrophytes. Most species of Cladocera found belong to the Chydoridae family, being typical inhabitants of the littoral zone, living associated with macrophytes. A total of 12 species were found, 9 of the subfamily Aloninae and 3 Chydorinae. In more than half of the water bodies the relative abundance of chydorids reached 100%, and they were dominant in most of the others, with few exceptions. Alona rustica was the most frequent species, occurring in 62% of the water bodies. The results evidenced the importance of the littoral zone as propitious habitats for the species of Chydoridae and contributing significantly to the diversity of Cladocera as a whole.